Mindfulness and Cognitive Flexibility as Predictors of Academic Self-Efficacy among Umm Al-Qura University Female Students - Alharbi, Hatun Ibrahim Saad; Alharbi, Nawar Mohammed Saad (Journal of Educational and Psychological Sciences, 2023)
The study aims to identify the level of mindfulness, cognitive flexibility and academic self-efficacy among Umm Al-Qura University female students and the predictability of academic self-efficacy through mindfulness and cognitive flexibility. The study sample consisted of (451) undergraduate female students from all disciplines, who were chosen using the random selection method. The study adopted the descriptive approach. To achieve the objectives of the study, the mindfulness scale prepared by Al-Harbi (2021), the cognitive flexibility scale prepared by Dennis and Vander Wal (2010), translated by Bishara (2020), and the academic self-efficacy scale by Ibrahim (2021) were applied. The results of the study showed an average level of mindfulness among Umm Al-Qura University female students. The results also indicated a high level of cognitive flexibility among the female students. The results showed as well that the academic self-efficacy level among Umm Al-Qura University female students was high. The results suggested that mindfulness contributes to a proper prediction of academic self-efficacy, and that cognitive flexibility also contributes to a proper and successful prediction of academic self-efficacy. In light of these results, the present study recommends including activities and strategies that develop the skills of cognitive flexibility and academic self-efficacy among female students, as well as raise their level of mindfulness in the curricula.
Keywords: Mindfulness; Cognitive Flexibility; Academic Self-Efficacy; Umm Al-Qura University Female Students